INADEQUATE POSTPRANDIAL COMPENSATORY TACHYCARDIA IN ELDERLY PEOPLE - Yousaf, Mohammad; Badar, Ahmed; Ansari, Ahmad Kamal (Journal of Ayub Medical College Abbottabad, 1996)
The effects of aging on cardiovascular and autonomic systems were evaluated through postprandial baroreceptor activity comparison between a group of young adults (n=20) and a group of elderly subjects (n=50) through measurements of pulse rate, which is an indicator of baroreceptor activity. Significant rise of pulse rate was observed in the young adults at 15, 30, 45 and 60 minutes after meal, while similar postprandial compensatory tachycardia was not found in the elderly group. The mean differences in pulse rate in young adult group at 15, 30, 45 and 60 minutes after meal were 2.05 ±0.28, 5.90 ±0.37, 5.95 ±0.37 and 3.60 ±0.42 beats /minute respectively, while the same values at the same time intervals in elderly subjects were 0.48±0.31, 1.14±0.54, 0.06 ±0.34 and -0.36±0.26 beats/minute respectively. Highly significant differences (p <0.001) were observed in the values at all postprandial time intervals between the two groups.